(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Algorithm means the sum of the sequence of calculation or problem solving processes. Algorithms do not depend on any programming language, they are instructions that lead to the same result even if the code is written in any language. But not all instructions are algorithms. To be an algorithm, an instruction has several characteristics.